A formação do leitor literário juvenil: uma proposta de diálogo entre o verbal e o visual - Silva, Sandra de Melo (2021)
The present work proposes a reflection on alternatives of contents and procedures for the formation of young literary readers in Middle School, through the dialogue between the works: The tale of the unknown island, by writer José Saramago, and the short film My friend Nietzsche, by director Fáuston da Silva. The goal of this proposal is to contribute to and develop the students’ interests and their interaction with literary reading and non-verbal text. To make the proposal viable, we chose texts that dialogue with each other. The study undertaken here and our experience with teaching has shown that this formation is increasingly necessary at all levels of basic education, as it helps in the human and cognitive development of the students. Considering the contemporary society, which increasingly demands proficient and critical readers, we developed, as a product of this research, reflective analysis that would improve the reading competence through literature and cinema. We believe that the analysis of the relationship between Literature and Cinema can broaden and enrich the author-text-reader interaction, providing the better development of interpretation, understanding, and reading skills. Our theoretical support includes Cosson (2014), Candido (2004), Aguiar and Bordini (1988), Zilberman (1989), Colomer (2007), Bakhtin (1986), Duarte (2002) Koch (2012), PCNs (1998), among others